Abnormal c-Fos expression in TetTag mice containing fos-EGFP - Wilmot, Jacob H.; Warren, Tracy L.; Diniz, Cassiano R. A. F.; Carda, Deger; Lafreniere, Marrisa M.; Nord, Alex S.; Wiltgen, Brian J. (Frontiers in Behavioral Neuroscience, 2024)
Molecular and genetic techniques now allow selective tagging and manipulation of the population of neurons, often referred to as “engram cells,” that were active during a specific experience. One common approach to labeling these cells is to use the fos-tTA transgenic mouse (TetTag). In addition to tagging cells active during learning, it is common to examine the reactivation of these cells using immediate early gene (IEG) expression as an index of neural activity. There are currently multiple TetTag lines available. The original line, cryopreserved at MMRRC, contains only the fos-tTA transgene, while Jackson Labs provides a version of the mouse that expresses both the fos-tTA and fos-shEGFP genes. In the current experiments, we examined IEG expression in these two mouse lines. Unexpectedly, we found that Jackson fos-tTA/fos-shEGFP mice express increased levels of c-Fos in the hippocampus compared to wild type animals when examined with immunohistochemistry (IHC). The expression of other IEGs, such as Arc and Egr-1, was not elevated in these mice, suggesting that the overexpression of c-Fos is not the result of increased excitability or broad changes in gene expression. qPCR revealed that Jackson fos-tTA/fos-shEGFP mice express mRNA corresponding to a c-Fos-Exon1-GFP fusion molecule, which may bind to C-Fos antibodies during IHC and inflate apparent c-Fos expression. Jackson fos-tTA/fos-shEGFP mice did not differ from their wild-type counterparts in fear expression or memory, indicating no behavioral effect of the presence of a c-Fos-GFP fusion protein. These results identify a major limitation inherent in the use of Jackson fos-tTA/fos-shEGFP mice.